3D hierarchically ordered composite block copolymer hollow sphere arrays by solution wetting - Fu, J.; Wang, J.; Li, Qin; Kim, D.H.; Knoll, W. (American Chemical Society, 2010)
Hierarchically ordered 3D arrays of block copolymer hollow spheres have been fabricated by using solution wetting of silica inverse colloidal crystals. Subsequent drying and annealing in the molten state yield nanopatterned shells due to the microphase separation of the block copolymers. The shell thickness can be controlled by properly selecting the polymer solution concentration, and the nanostructures inside the shells can be manipulated by varying molecular weights and/or compositions of the block copolymers. This versatile strategy can be readily applied to fabricate patterned metal (gold and palladium) nanoparticles inside the shells of the highly ordered hollow spheres. Thus, the locally ordered nanostructures of block copolymers are integrated into long-range 3D order defined by the silica inverse colloidal crystal templates, promising convenient fabrication of highly integrated devices.